KINERJA KEUANGAN, POLITICAL VISIBILITY, KETERGANTUNGAN PADA HUTANG TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN (Studi Empiris Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2013-2015) - Andi Affandi; Nur Diana (e_Jurnal Ilmiah Riset Akuntansi, 2017)
Abstract         The purpose of this study is to provide empirical evidence about the influence of financial performance, political visibility, reliance on debt to corporate social responsibility. The samples are manufacturing companies listed in Indonesia Stock Exchange (BEI) during the years 2013 to 2015 as many as 56 companies. Financial performance variables, political visibility and reliance on debt simultaneously or jointly significant effect on corporate social responsibility. The amount of influence , financial performance(ROA), political visibility (SIZE) and leverage (DER) against CSR is 10.1%. While the influence of the remaining 89.9% is explained by other variables outside the regression equation.Keyword : ROA, political visibility, leverage, corporate social responsibility